BILATERAL CHOROIDAL OSTEOMA: VISUAL ACUITY AT 45-YEAR FOLLOW-UP. Issue Volume 9:Issues 3(2015:Summer) (2015) - Hasanreisoglu, Murat; Shields, Jerry A.; Mashayekhi, Arman; Shields, Carol L.
Abstract : Purpose: To report a case of bilateral choroidal osteoma, which demonstrated different visual outcomes in both eyes over a long follow-up of 45 years. Methods: Case report. Results: After 45 years of follow-up, choroidal osteoma showed slight enlargement in each eye and choroidal neovascularization and retinal pigment epithelium (RPE) changes had developed in the right eye. Visual acuity of the right eye was decreased to 20/200 from macular RPE loss and choroidal neovascularization scarring. The left eye preserved a visual acuity of 20/30 where choroidal osteoma demonstrated only partial decalcification of the nasal margin with preservation of RPE in the macular region. Spectral domain optical coherence tomography of the right macula confirmed broad RPE and choroidal atrophy and scarring related to previous choroidal neovascularization. Spectral domain optical coherence tomography of the left macula showed preserved retinal layers and RPE with underlying calcified choroidal osteoma. Conclusion: Choroidal osteoma can occasionally demonstrate intact calcification, preserved RPE, and photoreceptors with excellent vision. Abstract : The authors report a patient with bilateral choroidal osteoma followed for 45 years. The right eye had extensive decalcification and poor vision, whereas the left eye demonstrated minimal macular decalcification, intact retinal pigment epithelium, and good vision.